Between Scylla and Charybdis: Theoretical Reﬂections on ‘The Protection of Intellectual Property Rights under International Investment Law’ by Klopschinski, Gibson and Ruse-Khan - D. K. Labin; A. V. Soloveva (Московский журнал международного права, 2022)
INTRODUCTION. The relationship between investment protection and intellectual property rights is one of the longstanding issues in international investment law — intellectual property rights have long been recognised as a form of ‘investment’ entitled to protection under bilateral investment treaties and other international investment agreements. The book co-authored by Simon Klopschinski, Christopher Gibson, and Henning Grosse Ruse-Khan, and entitled The Protection of Intellectual Property Rights under International Investment Law [Klopschinski, Gibson,Ruse-Khan 2021] provides a welcome contribution to the debate on the issue by addressing the problem from an informed theoretical standpoint. However, this issue, as correctly pointed out by the authors, is not merely a theoretical one, but rather one with signiﬁcant consequences in terms of the integration of other concerns and values in investment treaties and arbitral cases, such as intellectual property rights protection.MATERIALS AND METHODS. The materials for the article were the book co-authored by Simon Klopschinski, Christopher Gibson, and Henning Grosse Ruse-Khan, The Protection of Intellectual Property Rights under International Investment Law (2021), in light of the relevant academic literature in the ﬁeld of international investment law and IP. The methodological basis of the research consists of general scientiﬁc and special methods.RESEARCH RESULTS. Without doubt, this book is a comprehensive and stimulating study by the experts in both ﬁelds that will deepen understanding of the relationship between IP and investment. The authors masterfully bring together discourses that are taking place between scholars and practitioners in each regime, but frequently in relative isolation from each other.DISCUSSION AND CONCLUSIONS. With regard to the subject-matter, it is clear that no matter how specialised the ﬁelds of international law already are, and will increasingly become in the future, they maintain common roots and traits. Once this path of mutual exchange is taken, many positive cross-fertilisation eﬀects can be expected in the future. The greatest part of the book consists of an analysis of shared procedural and substantive norms. Klopschinski, Gibson and Ruse-Khan focus on how substantive provisions are articulated across the two legal regimes and identiﬁes commonalities and diﬀerences in framing and in how they are interpreted in dispute settlement.